Arterial blood velocity measurement by portable wireless system for healthcare evaluation: the related effects and significant reference data - Noor Azmi, Azran Azhim; Kinouchi, Yohsuke (Austria In-Tech, 2009)
Arterial hemodynamic function is changed with aging, gender and regular exercise. Age-related decrease in cardiovascular function are evident. The hallmarks of cardiovascular aging are decreased for maximum heart rate, rejection fraction, maximal oxygen intake, maximum cardiac output and artery compliance (Lakatta, 2002; Tanak etal, 2000). On the other hand, we have found that exercise could improve the age-related deterioration in common-carotid blood velocity (Azhim et al., 2007)